Supraventricular Arrhythmias after Thoracotomy: Is There a Role for Autonomic Imbalance? - George Vretzakis; Marina Simeoforidou; Konstantinos Stamoulis; Metaxia Bareka (Anesthesiology Research and Practice)
Supraventricular arrhythmias are common rhythm disturbances following pulmonary surgery. The overall incidence varies between 3.2% and 30% in the literature, while atrial fibrillation is the most common form. These arrhythmias usually have an uneventful clinical course and revert to normal sinus rhythm, usually before patent’s discharge from hospital. Their importance lies in the immediate hemodynamic consequences, the potential for systemic embolization and the consequent long-term need for prophylactic drug administration, and the increased cost of hospitalization. Their incidence is probably related to the magnitude of the performed operative procedure, occurring more frequently after pneumonectomy than after lobectomy. Investigators believe that surgical factors (irritation of the atria per se or on the ground of chronic inflammation of aged atria), direct injury to the anatomic structure of the autonomic nervous system in the thoracic cavity, and postthoracotomy pain may contribute independently or in association with each other to the development of these arrhythmias. This review discusses currently available information about the potential mechanisms and risk factors for these rhythm disturbances. The discussion is in particular focused on the role of postoperative pain and its relation to the autonomic imbalance, in an attempt to avoid or minimize discomfort with proper analgesia utilization.